The metamorphosis of home banking on people's power. [article]. - Ramos, Exaltacion C.
This paper discusses the transformation of a troubled business institution into a more dynamic, employee-and costumer-oriented one using Corporate Transformation Techniques which emphasize a spiritual change in the members of the corporation and hence of the corporation itself. Using a framework which stressed the need for values and vision, the New Management group established a new bank culture which attended to 1)structure, 2)in workshops, trainings, slogans, posters and skills. A new style making use of management openness, communication, staff training, frequent socials, etc.-all of which sought to develop a closer relationship between management and staff. Such a way, the New management group sought to build a fully functioning work team in a new human, more spiritual corporate setting.